THE STUDY OF TEMPORAL CHANGES ON LAND COVER/LAND USE PREVAILING IN BAGHDAD GOVERNORATE USING RS & GIS - & Muhaimeed, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was carried out in order to identify and mapping the temporal changes for land covers in Baghdad province using Remote Sensing and GIS. Three images were used of land sate taken in 1976, 2000 and 2014 the study area. Suppervised classification and SAVI Index were used to identify land cover classes dominated in the study area. The results of supper classification indicated the presence of five land cover classes including water bodies, bare land, urban, low dense vegetation, and dense vegetation classes. There were four classes of land cover when was used SAVI index: water, no vegetation (bare land and urban), low dense vegetation, and dense vegetation. The results showed that Remote Sensing is a very active and useful tool that can be used to detect land core types. The results showed a decline in class of water bodies from 2.8% to 1.5% for 1976 to 1990 while in 2014 increased to 2.1%. class Urban areas increased continuously with time and accounted for 17.6% , 23.5% and 28.2 % for years of study, indicating  the existence of the phenomenon of urban encroachment. Bare land areas accounted for 29.3% , 26.8% and 33.5% of stady years, respectively. The class of low dense vegetation decreased from 44.8% to 31.7% and 29.4% for 1976, 1990 and 2014 respectively, while the class-Dense vegetation increased at 1976-1990 from 5.5% to 16.4% and  decreased in 2014 to 6.8%. The SAVI had a role in the detection of agriculture and gave results same to the results of super classification. Results indicated that urban land and salinization process can be consider as the most phenomenon which negatively affected on agriculture area.